2005
DOI: 10.1111/j.1467-8454.2005.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

The Bilateral J‐curve: Australia Versus Her 23 Trading Partners

Abstract: Several studies have tested the J-curve phenomenon for Australia using non-stationary aggregate trade data and have provided mixed results. They not only suffer from the 'aggregation bias problem' but also from the 'spurious regression problem'. To overcome these problems, in this paper we investigate the short-run and the long-run effects of real depreciation of the Australian dollar on the trade balance between Australia and each of her 23 trading partners using quarterly data over the 1973-2001 period and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 24 publications
1
33
1
Order By: Relevance
“…Bahmani-Oskooee and Ratha (2004a) presents a very comprehensive survey on the J-curve literature for the period of . The recent examples of the J-curve studies include Arora, et al (2003), Onafowora (2003), Bahmani-Oskooee and Ratha (2004b), Bahmani-Oskooee et al (2005), Hacker andHatemi (2004), Narayan (2004), Narayan and Narayan (2004), Moura and Da Silva (2005), Bahmani-Oskooee et al (2006a), andBahmani-Oskooee andWang (2006b). Despite the well established theoretical the relationship between the exchange rate and the trade balance, the empirical results for this relationship are still inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Bahmani-Oskooee and Ratha (2004a) presents a very comprehensive survey on the J-curve literature for the period of . The recent examples of the J-curve studies include Arora, et al (2003), Onafowora (2003), Bahmani-Oskooee and Ratha (2004b), Bahmani-Oskooee et al (2005), Hacker andHatemi (2004), Narayan (2004), Narayan and Narayan (2004), Moura and Da Silva (2005), Bahmani-Oskooee et al (2006a), andBahmani-Oskooee andWang (2006b). Despite the well established theoretical the relationship between the exchange rate and the trade balance, the empirical results for this relationship are still inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Bahmani-Oskooee and Ratha (2004a) provides a very comprehensive survey on the J-curve literature for the period of 1973-2003 from thirtyseven articles. The recent examples of the J-curve studies include Bahmani-Oskooee et al (2006), Bahmani-Oskooee et al (2005), Bahmani-Oskooee and Ratha (2004b), Hacker and Hatemi (2004), , and Narayan and Narayan (2004). The empirical literature on the evidence of the J-curve, however, is fairly ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…3 Canada was one of Japan's major trading partners that was included in Bahmani- Oskooee and Goswami (2004) who found that in the bilateral import and export value models between Japan and Canada the real bilateral exchange rate was insignificant. However, Canada was also one of 20 major trading partners of U.K. included in Bahmani-Oskooee et al (2005a), who found that in the bilateral models between Canada and U.K., the real exchange rate was significant in the import value model but not in the export value model. Perhaps the most comprehensive study pertaining to Canada in this group is Bahmani-Oskooee et al (2005b) who estimated the import and export value models between Canada and each of her 20 major trading partners.…”
mentioning
confidence: 95%
“…The basic models in this group include the value of exports in one relation and the value of imports in another relation as the dependent variables. The list includes Haynes et al (1986), Cushman (1987Cushman ( , 1990, Bahmani-Oskooee and Goswami (2004), Bahmani-Oskooee et al (2005a, b), and Bahmani-Oskooee and Ardalani (2006).As far as Canada is concerned, it was one of G7 countries included in Cushman (1987) who found no significant price elasticities in import and export value models and concluded that "dollar devaluation could improve the U.S. trade balance most in the case of Japan, Italy, and the Netherlands, but could be ineffective or harmful in the cases of Canada, the U.K., and France.". 3 Canada was one of Japan's major trading partners that was included in Bahmani- Oskooee and Goswami (2004) who found that in the bilateral import and export value models between Japan and Canada the real bilateral exchange rate was insignificant.…”
mentioning
confidence: 99%
See 1 more Smart Citation